2020
DOI: 10.1002/jcp.30123
|View full text |Cite
|
Sign up to set email alerts
|

The new role for an old guy: MYC as an immunoplayer

Abstract: As an oncogene, myelocytomatosis oncogene (MYC) is implicated in the concept of “oncogene addiction,” where switching off the oncogene leads to the cell cycle arrest and cell differentiation. However, recent data suggest that MYC also controls the establishment of the tumour microenvironment and that “oncogene addiction” actually has a strong immune background. Evaluation of the MYC role in the immunoediting process led to the speculation that cancer just uses and distorts the physiological mechanism by which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…In addition to these cell intrinsic effects, MYC has also been shown to alter the tumor microenvironment and promote immune evasion [4,17,[55][56][57][58]. Thus in a mutant KRAS mouse model of liver cancer, Xu et al [17] showed that upregulation of MYC resulted in an influx of inflammatory cells such as neutrophils and macrophages into tumors.…”
Section: Role Of Myc In Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these cell intrinsic effects, MYC has also been shown to alter the tumor microenvironment and promote immune evasion [4,17,[55][56][57][58]. Thus in a mutant KRAS mouse model of liver cancer, Xu et al [17] showed that upregulation of MYC resulted in an influx of inflammatory cells such as neutrophils and macrophages into tumors.…”
Section: Role Of Myc In Tumorigenesismentioning
confidence: 99%
“…Consistent with MYC being a driver of tumorigenesis, suppression of its expression or inhibition of its function can reverse tumorigenesis [59][60][61][62][63]. This regression of tumorigenesis is mediated by reversal of the carcinogenic processes mentioned above, including, some or all of the following: promotion of cell cycle arrest, triggering of apoptosis, induction of senescence, promotion of differentiation, inhibition of angiogenesis, extrusion of tumor infiltrating inflammatory cells such as macrophages and neutrophils, influx of T and NK cells, reduced levels of PD-L1 and upregulation of an anti-tumor immune response [4,[55][56][57][58]. Indeed, in some situations, even brief or partial suppression of MYC has been shown to reverse tumorigenesis [4,58,59].…”
Section: Role Of Myc In Tumorigenesismentioning
confidence: 99%
“…Accordingly, flow cytometric analysis of the isolated 100% CD44-positive ECSC populations revealed over 93% positive PD-L1 and 99% PD-L2 expressing cells, substantiating the link between stemness and immune evasion of ECSCs. Accordingly, the proto-oncogene MYC has been shown to contribute to immunosuppression by directly inducing PD-L1 expression, while the downregulation of MYC led to immune cell infiltration (reviewed in [ 39 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Although MYCN is distinct from MYC (c-myc) [33,34], they are known to share prominent but incomplete redundancy [31]. Recent studies indicate that MYC not only acts as an oncogene but also directly regulates immune responses by various mechanisms that facilitate immune evasion and immunosuppression [35][36][37]. However, whether MYCN in NBL exerts a similar effect on immune regulation as MYC does in other cancers remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%